Culture of Class Radio and Cinema in the Making of a Divided Argentina, 1920-1946 - Karush, Matthew B. (Matthew Benjamin), 1968-; Project Muse. (Duke University Press, 2012)
Major change came to Argentina during the first decades of the twentieth century. Following the mass influx of European immigrants to the country during the beginning of the century, a truly national culture was produced through mass media, facilitating the assimilation of immigrants and their descendants. New forms of media emerged, such as radio and cinema, as did new forms of entertainment, such as tango songs, films, and radio theater. Yet despite the unifying effect of popular culture, the nation remained divided, and, if anything, more so in 1950 than in 1910. This book argues that the key to understanding this paradox lies in a reassessment of the mass culture of the 1920s and 1930s. With a focus on film and radio in and around Buenos Aires, the locus of production as well as much of the market consumption, Karush shows how integration and class fractures occurred simultaneously in a short span of the country's history. He brings together the usually separated subjects of radio and cinema to show how they can combine to gauge a larger cultural and political environment and shed light on class distinctions. The book contributes to an ongoing discussion of the relationship between power and mass culture. It will be of interest to scholars of cultural history and urban studies and those interested in Latin American history and culture.
Class formation in the barrios -- Competing in the transnational marketplace -- Repackaging popular melodrama -- Mass-cultural nation building -- Politicizing populism -- Epilogue: The rise of the middle class, 1955-1976.
Includes bibliographical references (p. [251]-268) and index.
Description based on print version record.
Keywords: Radio broadcasting -- Argentina -- History -- 20th century; Motion pictures -- Argentina -- History -- 20th century; Popular culture -- Argentina -- History -- 20th century; Social classes -- Argentina -- History -- 20th century; Electronic books